Transmission of multidrug-resistant Mycobacterium tuberculosis is reality in Switzerland - Niederer-Loher, Anita; Kahlert, Christian; Barben, Jürg; Deggim, Vanessa; Zellweger, Jean-Pierre (Journal of Pediatric Infectious Diseases, 2012)
We report the first documented patient-to-patient transmission of Multidrug resistant tuberculosis observed in Switzerland between two young, previously healthy patients from Tibet. They both lived in Switzerland for several years and did not originate from the same community. Resistance patterns and restriction fragment length polymorphism-analysis (RFLP-analysis) of both strains were identical.
Keywords: Tuberculosis; multidrug-resistance; transmission; contact-investigation